Disciplinarisation des comportements musulmans dans l'espace public. Pratiques musulmanes et entreprises d'étiquetage à Rennes, Bristol, Nantes et Glasgow - Alice Picard (Revue Française de Civilisation Britannique)
The study of the governance of Islam in four cities in France and in the United Kingdom reveals convergences on both sides of the Channel, despite national models that are often presented at odds with each other. Whether it be the mobilisation by some part of the laïque1 voluntary sector in Rennes and Nantes or the recentralisation of the governance of the counter-extremism policy Prevent by the British government, both phenomena result in the disciplinary government of Muslim conduct in public spaces. In the four case studies, and in spite of various degrees of resistance, grassroots players, both professionals and volunteers, are encouraged by city and government authorities to consider Muslim orthodoxy and orthopraxis as deviant conduct with regard to secular norms, and in some cases even as signs of radicalisation that pose a threat to public order and therefore call for exceptional measures.